2021
DOI: 10.1111/asj.13527
|View full text |Cite
|
Sign up to set email alerts
|

Complement C3 participates in the development of goose fatty liver potentially by regulating the expression of FASN and ETNK1

Abstract: Non-alcoholic fatty liver disease (NAFLD) occurs in humans, domestic animals and poultry. Different from upregulation of complement C3 in human NAFLD, C3 expression is inhibited in goose fatty liver (GFL), implying a specific role of C3 in GFL. This study was mainly focused on uncovering the uniqueness of goose liver cells in the regulation of C3 expression and identifying the downstream genes of C3 to improve understanding on the specific role of C3 in GFL. The results showed that C3 expression was inhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Complement C3 affects both steatosis and the inflammatory response in the liver. Even with 60% liver fat, geese do not show inflammatory or pathogenic features, due to C3 representative downstream genes of C3 (FASN and ETNK1) that regulate C3 function [ 40 ]. In addition to obesity, a study of 2815 nondiabetic healthy middle-aged men with long follow-up plasma protein analysis showed that complement C3 levels were associated with the risk of developing diabetes [ 41 ].…”
Section: Complement and Agingmentioning
confidence: 99%
“…Complement C3 affects both steatosis and the inflammatory response in the liver. Even with 60% liver fat, geese do not show inflammatory or pathogenic features, due to C3 representative downstream genes of C3 (FASN and ETNK1) that regulate C3 function [ 40 ]. In addition to obesity, a study of 2815 nondiabetic healthy middle-aged men with long follow-up plasma protein analysis showed that complement C3 levels were associated with the risk of developing diabetes [ 41 ].…”
Section: Complement and Agingmentioning
confidence: 99%
“…Goose fatty liver (foie-gras) is a well-known delicacy and an unsaturated fatty acid-rich food composed of 50–60% lipids, which is produced using geese or ducks fed a diet rich in high-energy carbohydrates, where excess glucose is converted to fat via de novo lipogenesis in the liver, mainly in the form of TG [ 17 , 18 , 19 , 20 ]. The Landes goose is famous for production of foie-gras because it can store large amounts of fat in its liver [ 17 , 18 , 19 , 20 ].Interestingly, we found that betaine reduced sebum thickness and abdominal fat in Landes geese fed with high-energy carbohydrates, but increased liver weight due to fat accumulation [ 21 ]. Betaine also resulted in uniform lipid deposition, with a significant reduction in the number and volume of large lipid droplets [ 21 ].…”
Section: Introductionmentioning
confidence: 99%